2009
DOI: 10.1007/s10534-009-9221-8
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures, antioxidation and DNA binding properties of Yb(III) complexes with Schiff-base ligands derived from 8-hydroxyquinoline-2-carbaldehyde and four aroylhydrazines

Abstract: X-ray crystal and other structural analyses indicate that Yb(III) and all four newly synthesized ligands can form a binuclear Yb(III) complex with a 1:1 metal to ligand stoichiometry by octacoordination at the Yb(III) center. Investigations of DNA binding properties show that all the ligands and Yb(III) complexes can bind to Calf thymus DNA through intercalations with the binding constants at the order of magnitude 10(5)-10(7) M(-1), but Yb(III) complexes present stronger affinities to DNA than ligands. All th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The differences in the deprotonization and enolization may well be due to the fact that triethylamine was added into the reaction mixtures to deprotonate the phenolic hydroxyl substituent of 8-hydroxyquinolinato unit in the formation of the Eu(III) complex. However, carbonyl group C@O directly linking with aromatic group may be favorable of enolizing under the present experimental conditions, so as to form a larger conjugated and a lower energy system, than the non-aromatic group such as -NH 2 when binding to metal ion and forming a complex [25]. It is the enolization and deprotonation of O@C-NH-group changing into À O-C@N-that the [HoL 1 (NO 3 )(DMF) 2 ] 2 complex is of neutral charge and non-electrolyte, but both of [YL(NO 3 )(DMF) 2 ] 2 Cl 2 Á2(DMF) and [LaL(NO 3 )-(MeOH) 2 ] 2 (NO 3 ) 2 complexes are of electrolytes.…”
Section: The Crystal Structure Of Complex 2amentioning
confidence: 85%
“…The differences in the deprotonization and enolization may well be due to the fact that triethylamine was added into the reaction mixtures to deprotonate the phenolic hydroxyl substituent of 8-hydroxyquinolinato unit in the formation of the Eu(III) complex. However, carbonyl group C@O directly linking with aromatic group may be favorable of enolizing under the present experimental conditions, so as to form a larger conjugated and a lower energy system, than the non-aromatic group such as -NH 2 when binding to metal ion and forming a complex [25]. It is the enolization and deprotonation of O@C-NH-group changing into À O-C@N-that the [HoL 1 (NO 3 )(DMF) 2 ] 2 complex is of neutral charge and non-electrolyte, but both of [YL(NO 3 )(DMF) 2 ] 2 Cl 2 Á2(DMF) and [LaL(NO 3 )-(MeOH) 2 ] 2 (NO 3 ) 2 complexes are of electrolytes.…”
Section: The Crystal Structure Of Complex 2amentioning
confidence: 85%
“…Both excitation and emission band widths were 10 nm. DNA-EB quenching assay was performed according to literature procedure [19,20]. DNA (4.0 mmol L À1 , nucleotides) solution was added incrementally to 0.32 mmol L À1 EB solution, then small aliquots of concentrated solutions (1.0 mmolL À1 ) were added till the drop in fluorescence intensity ( ex ¼ 525 nm, em ¼ 587 nm) reached a constant value.…”
Section: Methodsmentioning
confidence: 99%
“…All these ligands and rare-earth metal complexes showed strong anti-oxidation and DNA-binding properties, useful as potential anticancer drugs [19][20][21][22][23][24]. In this article, the Schiff base derived from 8-hydroxyquinoline-7-carbaldehyde with isonicotinylhydrazine and its lanthanide(III) complexes are prepared to investigate their anti-oxidation and DNAbinding properties.…”
Section: Dna-binding and Anti-oxidation Properties Of Binuclear Lanthmentioning
confidence: 99%
“…We found that all these ligands and rare-earth metal complexes showed stronger antioxidation and DNA binding properties. [15][16][17][18] However, there were different structures and biological properties between these metal complexes. In this paper, the Tb(III) complexes were prepared from Tb(NO 3 ) 3 Á6H 2 O with the four Schiff-base ligands and their antioxidation, DNA binding properties, and Tb(III) luminescence with these systems were investigated.…”
Section: Introductionmentioning
confidence: 99%